Status of the SPHERE project for high energy cosmic ray studies by registering reflected Cherenkov light with a drone-borne detector. Issue 1 (1st November 2022) - Chernov, D.; Bonvech, E.; Finger, M.; Finger, M.; Galkin, V.; Ivanov, V.; Latypova, V.; Podgrudkov, D.; Roganova, T.; Vaiman, I.
Abstract : Here we present the current state of the technical design of the SPHERE project's new detector. The SPHERE project is aimed at primary cosmic ray studies in the 1–1000 PeV energy range using the reflected Cherenkov light method. The concept of a drone mounted detector with a photosensitive camera based on silicon photomultipliers is discussed. The design details of a small scale prototype of this detector is presented.